Análisis e Interpretación a los Estados Financieros de la Compañía de Transporte Pesado “Ciudad de Loja” Copeloja Cía. Ltda, Matriz Loja, Períodos 2014 – 2015. Propuesta de Mejoramiento - Quishpe Malla, Soraya Vanessa (2017)
The thesis work called "ANALYSIS AND INTERPRETATION TO THE FINANCIAL STATEMENTS OF THE HEAVY DUTY COMPANY" CIUDAD DE LOJA "COPELOJA CÍA. LTDA, MATRIX SHOP, PERIODS 2014 - 2015. PROPOSAL FOR IMPROVEMENT ", has the purpose of establishing the economic and financial position, for the correct management decision-making of the Company, which was carried out in compliance with the Regulation of Academic Status in force National University of Loja, prior requisite to obtain the title of Engineer in Accounting and Auditing Public Accountant-Auditor. In compliance with the first specific objective, the vertical analysis was applied, taking the corresponding values of each account of the statement of financial position and of the income statement, with reference to the base value, a result that is multiplied by one hundred, to determine the percentage participation Which has each of the accounts within the economic and financial situation of the Company; And the horizontal analysis determined increases and decreases in the individual accounts of each financial statement, by means of the difference between the partial value of the current year and the partial value of the last year, allowing to record the existing changes in absolute values and values Relative to the period 2014 and 2015. 6 The second specific objective is to apply financial indicators of the Superintendency of Companies, Securities and Insurance, the liquidity indicator consented to establish the facility or difficulty that the Company presents to pay its current liabilities by converting its current assets into cash; The activity indicator was in charge of measuring the efficiency with which the company uses its economic resources; The profitability indicator allowed to know the effectiveness of the administration in the control of the expenses and the generation of profit; And the indebtedness indicator established the degree of participation of the creditors within the financing of the Company. The third specific objective is to prepare the financial report and the improvement proposal based on the results obtained, presenting possible solutions so that the executives based on the proposed take correct decisions to have an efficient administration that leads to the satisfaction of customers for the provision of services. Finally, the most relevant conclusion after applying the analysis and interpretation to the financial statements is that the Company has high operating expenses, due to the fact that in 2014 they have a value of $ 461,752.26, which means 96.82% of total expenses and Income for the year, while operating income is $ 436,910.45 equivalent to 91.52% of total income; And, in 2015, the expenses generated by the activity are valued at 7 $ 425,241.89, representing 96.35% of total expenses and income for the year, while operating income is $ 400,195.28, equivalent to $ 90.67 % Of total income, showing that the expenses resulting from the financial analysis have values higher than the revenues originating from the main activity of the Company. This is due to the absence of a control of the expenses, especially in the account transport that both years is of greater representativity, generated by several factors during the route of the transport of the merchandise, like parking and storage, fuel, tires, diets , Among others, which produces a net profit below the requirements expected in the partners, therefore it is recommended to the Company's managers to reduce selling expenses and establish as a policy in all areas the optimization of material resources And financial resources to achieve the adequate return in proportion to the activity.